Cahaya Al-Qur’an di Tengah Derasnya Arus Informasi: Solusi Mencegah Hoaks di Era Digital - M. Rayhan; Achmad Abubakar; Muhsin Mahfudz (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
In the digital era, the spread of false information or hoaxes has become increasingly rampant, particularly through social media. This phenomenon has negative impacts on society as it can trigger division and social unrest. In addressing this issue, the Qur’an offers valuable guidance. This study aims to identify the solutions proposed in the Qur’an to prevent the dissemination of hoaxes. The research employs a qualitative approach using a literature review method. The Qur’an introduces the principle of tabayyun (verification), as stated in Surah al-Hujurat/49:6, which emphasizes the importance of verifying information before drawing conclusions about its truth. Furthermore, the Qur’an highlights the virtue of honesty as a means to prevent the spread of false news, as mentioned in Surah al-Ahzab/33:71. Islam also teaches the attitude of tawaqquf—refraining from sharing information whose authenticity is uncertain—as outlined in Surah al-Isra/17:36. Thus, Islamic teachings provide a comprehensive framework for fostering information literacy and ethical media behavior in the digital age.